2014
DOI: 10.1177/0333102414534083
|View full text |Cite
|
Sign up to set email alerts
|

The role of large-conductance, calcium-activated potassium channels in a rat model of trigeminal neuropathic pain

Abstract: Our results indicate the important involvement of mainly ERK and p38 MAPK pathways in modulating BKCa channels in ION-CCI TG neurons. BKCa channels represent a new therapeutic target for the clinical treatment of trigeminal neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…In our model, enhanced asymmetric face-grooming was observed in dIoN-CCI rats over a prolonged period of time. In contrast, the nociceptive behavior of rats subjected to previous IoN-CCI procedures varies depending on the specific type of procedure used in different studies 6, 13, 16, 17 . Some studies showed that IoN-CCI rats exhibited an early phase hyposensitivity and a late phase hypersensitivity to mechanical stimulation in the IoN territory 13, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In our model, enhanced asymmetric face-grooming was observed in dIoN-CCI rats over a prolonged period of time. In contrast, the nociceptive behavior of rats subjected to previous IoN-CCI procedures varies depending on the specific type of procedure used in different studies 6, 13, 16, 17 . Some studies showed that IoN-CCI rats exhibited an early phase hyposensitivity and a late phase hypersensitivity to mechanical stimulation in the IoN territory 13, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This multifunctionality can be an optimal strategy for the construction of biologically active peptides allowing sea anemones to be active predators through the production of neurotoxins and resist bacterial infections caused by the eventual injury of the tentacles. It is noteworthy that human β-defensin 2 (Hbd-2), the structural homologue of Ueq 12-1, possess antimicrobial properties, act as an opener of large-conductance Ca 2+ -activated potassium (BKCa)-mSlo+hβ1 channels and inhibit Kv1.3-channels [38,51,52]. These studies highlight the multifunctionality observed for this particular spatial fold.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of ERK and c-fos after estrogen replacement in ovariectomized CFA rats ERK is one member of the mitogen-activated protein kinase (MAPK) family, which is known to have different functions in sensory processing [33][34][35]. In the present study, the expressions of ERKand c-fosin the sham, OVX, and estrogen-treated CFArats were investigated.…”
Section: Estrogen Replacement Reversed the Decrease Of Pwt In Ovariecmentioning
confidence: 92%